Strategies of Ma'had Leaders in Enhancing Teacher Motivation and Performance in Integrated Tahfiz-Vocational Education - Ilham Nur Rachmadi; Ida Faridah (Al-Qalam Institue, 2026)
The integration of Tahfiz and Technical and Vocational Education and Training (TVET) curricula necessitates dual competencies for teachers, frequently precipitating excessive workloads and professional burnout, and potentially jeopardizing the objectives of the National Tahfiz Education Policy (DPTN) 2.0. This research aims to analyze the leadership strategies at Ma'had Tahfiz Vokasional Aman Bistari (MTVAB), Malaysia, in mitigating these challenges. Utilizing an exploratory single case study design, data were collected through methodological triangulation involving in-depth interviews, participant observation, and document review, and were subsequently analyzed using the Miles, Huberman, and Saldana model. The results reveal the implementation of a